The urban development of Istanbul in the nineteenth century: The role of expropriations - İbidan, Zuhal. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
This thesis examines the expropriation activities which were the most important tools for the government in the process of reconstruction implemented in Istanbul in the nineteenth century. The information in this thesis is generally based on the Ottoman archival records. In addition to this, some newspapers like Takvîm-i Vakayi’, Basîret and Tasvîr–i Efkâr and secondary sources were used. In the thesis, questions such as, what the purpose of this reconstruction plan and expropriations was, in which places of the capital city the plans were applied, by whom and how these plans were applied have been answered. Also addressed were issues such as what the government was aiming at by these expropriations and reconstruction plans, what was gained and how the public reacted towards these novelties. This thesis argues that the urban development which is at the intersection of centralization and modernization, and the concept of modern expropriation was a consequence of the change in the perspective and the understanding of the Ottoman government. Additionally, in the thesis, while the concept of modern expropriation is being evaluated in relation to the transformation in the governmental and legal mentality, the economic and social aspects of the expropriations are also emphasized. Other reconstruction processes occurring in other cities in the Ottoman Empire and other European cities which were taken as models in the reconstruction process of the capital city were investigated and documented here for the sake of approaching the expropriations from a comparative angle.
Keywords: City planning -- Turkey -- Istanbul.